Given the points: \( P(-1 ; 4), Q(2 ; 7), R(-3 ; 2) \) and \( S(m ;-1) \), solve for a) \( P Q \) is parallel to \( R S \) b) \( P Q \) is perpendicular to \( R S \).
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To find the value of \( m \) in both scenarios for the points \( P(-1, 4), Q(2, 7), R(-3, 2) \), and \( S(m, -1) \), we first need to calculate the slopes of the lines formed by these points. **a)** For \( PQ \) to be parallel to \( RS \), the slopes must be equal. 1. **Calculate the slope of \( PQ \)**: \[ \text{slope of } PQ = \frac{y_2 - y_1}{x_2 - x_1} = \frac{7 - 4}{2 - (-1)} = \frac{3}{3} = 1 \] 2. **Calculate the slope of \( RS \)**: \[ \text{slope of } RS = \frac{-1 - 2}{m - (-3)} = \frac{-3}{m + 3} \] 3. **Set the slopes equal**: \[ 1 = \frac{-3}{m + 3} \] Cross-multiplying gives: \[ m + 3 = -3 \implies m = -6 \] **b)** For \( PQ \) to be perpendicular to \( RS \), the product of their slopes must be -1. 1. **Slope of \( PQ \)** (already calculated): \[ \text{slope of } PQ = 1 \] 2. **Using the slope of \( RS \)**: \[ \text{slope of } RS = \frac{-3}{m + 3} \] 3. **Set the product of slopes to -1**: \[ 1 \cdot \frac{-3}{m + 3} = -1 \] Solving gives: \[ \frac{-3}{m + 3} = -1 \implies -3 = -1(m + 3) \implies -3 = -m - 3 \implies m = 0 \] In summary: - For \( PQ \parallel RS \), \( m = -6 \). - For \( PQ \perp RS \), \( m = 0 \).